2015
DOI: 10.1088/0004-637x/802/1/2
|View full text |Cite
|
Sign up to set email alerts
|

A STATISTICAL STUDY OF THE SOLAR WIND TURBULENCE AT ION KINETIC SCALES USING THEK-FILTERING TECHNIQUE AND CLUSTER DATA

Abstract: Plasma turbulence at ion kinetic scales in the solar wind is investigated using the multi-point magnetometer data from the Cluster spacecraft. By applying the k-filtering method, we are able to estimate the full three-dimensional power spectral density P (ω sc , k) at a certain spacecraft frequency ω sc in wavevector (k) space. By using the wavevector at the maximum power in P (ω sc , k) at each sampling frequency ω sc and the Doppler shifted frequency ω pla in the solar wind frame, the dispersion plot ω pla =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 66 publications
5
60
0
Order By: Relevance
“…The mean bulk speed of the solar wind is 655 ± 15 km s −1 , the mean proton density is low 2.8 ± 0.2 cm −3 , and plasma β = 0.85 ± 0.29. There are no interplanetary coronal mass ejections or stream interaction regions recorded at the time of the interval, and the large scale from Active Composition Explorer (ACE) data (not shown) suggests that this interval can be regarded as typical of the fast solar wind (see Roberts et al, 2015).…”
Section: Weakly Compressible Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean bulk speed of the solar wind is 655 ± 15 km s −1 , the mean proton density is low 2.8 ± 0.2 cm −3 , and plasma β = 0.85 ± 0.29. There are no interplanetary coronal mass ejections or stream interaction regions recorded at the time of the interval, and the large scale from Active Composition Explorer (ACE) data (not shown) suggests that this interval can be regarded as typical of the fast solar wind (see Roberts et al, 2015).…”
Section: Weakly Compressible Eventmentioning
confidence: 99%
“…Several multi-spacecraft observations of the solar wind have revealed that the fluctuations at proton kinetic scales typically have low intrinsic propagation speeds in the plasma frame. This result has been interpreted as evidence of kinetic Alfvén waves (KAWs) (Sahraoui et al, 2010), as coherent structures which are predominantly advected with the bulk velocity (Perrone et al, 2017), as a combination of KAW turbulence and coherent structures (Roberts et al, 2013(Roberts et al, , 2015, or as nonlinear modes where wave-wave interactions have broadened the dispersion relation diagram (Narita and Motschmann, 2017;Roberts et al, 2017). Kinetic slow waves (KSWs) are the kinetic counterpart of the magnetohydrodynamic (MHD) slow mode when it develops a large perpendicular wave number, and it shares many properties with the KAW, such as a similar dispersion relation and anticorrelated fluctuations in magnetic field and density Narita and Marsch, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This has variously been interpreted as evidence of quasi-linear waves that propagate slowly in the plasma frame (such as the quasi-perpendicular Kinetic Alfvén Wave (Sahraoui et al 2010)) or coherent structures with k ⊥ ≫ k which are advected by the plasma bulk flow or a combination of these two phenomena (Roberts et al 2013(Roberts et al , 2015. However, in the present work, by looking directly at the magnetic fluctuations around ion scales in the region of high intermittency, it has been clearly shown that the considered time interval is covered by coherent structures (making up ∼ 30% of the interval).…”
mentioning
confidence: 99%
“…Its validity has been supported by the gyrokinetic simulations (i.e., Howes et al 2011b). The quasilinear premise has been widely used to distinguish the wave modes in the dissipation range of the solar wind turbulence (e.g., Sahraoui et al 2010;He et al 2011;Salem et al 2012;Podesta 2013;Roberts et al 2013Roberts et al , 2015, as well in modeling the kinetic Alfvén turbulence (i.e., Schekochihin et al 2009;Howes et al 2011a;Voitenko and De Keyser 2011;Boldyrev & Perez 2012;Zhao et al 2013). The related assumption of the critical balance between the linear Alfvén propagation timescale and the nonlinear turnover timescales (Goldreich & Sridhar 1995) is also regularly used in modeling the strong Alfvénic turbulence.…”
Section: Damping Effectsmentioning
confidence: 99%
“…Alfvénic turbulence, measured in situ by satellites in the Earth's space environment (Chaston et al 2008(Chaston et al , 2009Huang et al 2012Huang et al , 2014 and in the solar wind (Sahraoui et al 2010;He et al 2011He et al , 2013Alexandrova et al 2012;Horbury et al 2012;Salem et al 2012;Podesta 2013;Roberts et al 2013Roberts et al , 2015, extends from magnetohydrodynamic (MHD) scales down to ion and even electron kinetic scales. Turbulence at kinetic scales is often referred to as kinetic Alfvén turbulence.…”
Section: Introductionmentioning
confidence: 99%